Treatment of Infantile Spasm Syndrome: Update from the Interdisciplinary Guideline Committee Coordinated by the German-Speaking Society of Neuropediatrics - Ramantani, Georgia; Bölsterli, Bigna K.; Alber, Michael; Klepper, Joerg; Korinthenberg, Rudolf; Kurlemann, Gerhard; Tibussek, Daniel; Wolff, Markus; Schmitt, Bernhard (Neuropediatrics, 2022)
Objectives The manuscript serves as an update on the current management practices for infantile spasm syndrome (ISS). It includes a detailed summary of the level of current evidence of different treatment options for ISS and gives recommendations for the treatment and care of patients with ISS.Methods A literature search was performed using the Cochrane and Medline Databases (2014 to July 2020). All studies were objectively rated using the Scottish Intercollegiate Guidelines Network. For recommendations, the evidence from these studies was combined with the evidence from studies used in the 2014 guideline.Recommendations If ISS is suspected, electroencephalography (EEG) should be performed within a few days and, if confirmed, treatment should be initiated immediately. Response to first-line treatment should be evaluated clinically and electroencephalographically after 14 days. The preferred first-line treatment for ISS consists of either hormone-based monotherapy (AdrenoCorticoTropic Hormone [ACTH] or prednisolone) or a combination of hormone and vigabatrin. Children with tuberous sclerosis complex and those with contraindications against hormone treatment should be treated with vigabatrin. If first-line drugs are ineffective, second-line treatment options such as ketogenic dietary therapies, sulthiame, topiramate, valproate, zonisamide, or benzodiazepines should be considered. Children refractory to drug therapy should be evaluated early for epilepsy surgery, especially if focal brain lesions are present. Parents should be informed about the disease, the efficacy and adverse effects of the medication, and support options for the family. Regular follow-up controls are recommended.
Keywords: epilepsy; infantile spasms; infantile spasm syndrome; West syndrome; guideline